Adsorption performance and its mechanism of aqueous As(III) on polyporous calcined oyster shell‐supported Fe–Mn binary oxide. (20th April 2022) - Shi, Yao; Xing, Yifei; Song, Zhilian; Dang, Xueming; Zhao, Huimin
Abstract: Fe–Mn binary oxide (FMBO) is a promising adsorbent for As(III) removal through combined adsorption and oxidation. The calcined oyster shell‐supported Fe–Mn binary oxide (FMBO/OS) adsorbent was synthesized by the co‐precipitation method. Results indicated that the calcined oyster shell, as a carrier, improved the stability of FMBO and its adsorption capacity for As(III). The maximum adsorption capacity of FMBO/OS on As(III) reached 140.5 mg·g −1 . Under pH 5.0 and 25°C, the removal efficiency of FMBO/OS to As(III) solution (C0  = 10 mg·L −1 ) reached 87% within 12 h. Moreover, based on the characterization analyses, the removal mechanisms of As(III) were deduced to include the combined adsorption and oxidation process of FMBO and the synergistic effect of oyster shells. This work provides new insights into synthesizing efficient and green adsorbents to remove aqueous As(III). Meanwhile, it provides technical support for reusing waste biomass materials such as the oyster shell. Practitioner Points: FMBO/OS was prepared by a simple hydrothermal co‐precipitation method. The carrier alleviates the agglomeration of Fe–Mn oxides. The adsorbent shows a strong adsorption capacity of As(III) and good selectivity. The good results benefit from the synergistic effect of calcium arsenate generation. The prepared adsorbent can adsorb arsenic in real samples. Abstract : This work reports a porous calcined oyster shell composite loaded with iron‐manganese binary oxides. It can effectively remove As(III) from water through the synergistic effect of adsorption and oxidation.